Between the margins and the mainstream: the odyssey of women in Greek and Yorùbá thoughts (2017)
Scholars have generally appraised issues relating to women from the viewpoint of gender inequalities and claimed that the female folk are largely oppressed by their male counterparts. Without doubt, the twenty-first century has witnessed gender relations characterized by a lot of imbalances especially to the detriment of women. However, studies have shown that in many societies, women enjoy some undeniable rights, and that prior to slave trade, colonialism and the advent of the missionaries in Africa, Yoruba women of Southwest Nigeria enjoyed certain privileges as much as their male counterparts and such as demanded by Plato in his 'ideal state'. This paper investigates the ideal roles and status of women from historical, religious, philosophical and cultural perspectives of the Yoruba people and compares their phenomenon with those of the ancient Athens as projected by Plato. Examining the rights of women from these two socio-cultural milieus, the paper establishes when and how gender inequality became a subject of debate in the histories of the Greek and the Yoruba people